Hungarian Monitoring, 6 December 1989 . [Magyar rádiófigyelő], 1989. december 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - GDR: national roundtable talks; incidents in the provinces - Czechoslovakia: premier resigns; shopping tourism - Soviet economic problems - Attempted putsch in Manila Domestic Affairs: - American Jewish Congress delegation visits Parliament - Election campaign - Accident at Gabčíkovo-Nagymaros dam - Hungarian Socialist Workers' Party (MSZMP) property accounts Economy: - Accelerated bankruptcy proceedings against loss-making companies - IMF talks - Tamás Beck's visit to Israel Külpolitika: - NDK: nemzeti kerekasztal megbeszélések; vidéki incidensek - Csehszlovákia: lemondott a miniszterelnök; bevásárló turizmus - Szovjet gazdasági problémák - Manilai puccskísérlet Belpolitika: - Az Amerikai Zsidó Kongresszus küldöttségének parlamenti látogatása - Választási kampány - Baleset Bősnél - MSZMP vagyonelszámolás Gazdaság: - Gyorsított csődeljárás a veszteséges vállalatoknak - Valutalap tárgyalások - Beck Tamás izraeli útja